(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Nowadays, language learning in any form (via social networks, courses, training, with the help of a teacher, audiovisual, etc.) is open to many people, and the offers are more and more consumer-oriented. There are various methods of quickly and effectively teaching and learning the language as a foreign language. Of all the methods of teaching and learning the language as a foreign language, it has always been used on a large scale, and it is aimed at meeting the needs of the respondents who are learning the language in the process of mastering the language as a foreign language. The uniqueness of language learning methods is directly related to individual and group psychology.